Long Non-Coding RNA in Drug Resistance of Non-Small Cell Lung Cancer: A Mini Review - Sun, Ruizheng; Wang, Ranran; Chang, Siyuan; Li, Kexin; Sun, Rongsi; Wang, Mengnan; Li, Zheng (Frontiers in Pharmacology, 2019)
Lung cancer is one of main causes of cancer mortality and 83% of lung cancer cases are classified as non-small cell lung cancer (NSCLC). Patients with NSCLC usually have a poor prognosis and one of the leading causes is drug resistance. With the progress of drug therapy, the emergence and development of drug resistance affected the prognosis of patients severely. Accumulating evidence reveals that long non-coding RNAs (lncRNAs), as “dark matters” of the human genome, is of great significance to drug resistance in NSCLC. Herein, we review the role of lncRNAs in drug resistance in NSCLC.